Functional characterization of alcohol dehydrogenase genes in Arabidopsis plants grown under drought condition - Myint, Thawda (2013)
In response to drought, plants change their metabolic activities towards limiting cellular water consumption and loss. One metabolic process that is affected by this stress is ethanolic fermentation. In plants, ethanolic fermentation occurs during limited oxygen condition and under certain environmental stresses. The effects of ethanol fermentation on plant growth and survival under drought stress are not well explained. In addition, previous studies on ethanolic fermentation in plants were limited to alcohol dehydrogense (EC.1.1.1.1) enzyme activity and gene expression. In this study, it was hypothesized that ethanolic fermentation is required to enhance plant ability to retain cellular water under drought. Enhancing the capacity of ethanolic fermentation in a plant would improve the plant ability to retain cellular water; thus, retain the plant’s photosynthetic capacity. To test the hypothesis, this study was carried out with the following objectives: i) to identify the specific ADH genes responding to drought in Arabidopsis plants, ii) to evaluate the effects of defective ADH on growth and drought-related parameters, iii) to evaluate the effects of enhanced ethanolic fermentation on growth and drought-related parameters. The objectives were achieved by a combination of the gain-and the loss-of-function approaches. For the gain-of-function approach, an Arabidopsis plant over-expressing the ADH1 transgene was developed using the Gateway technology where fully characterized homozygous lines were used for the analysis. As for the loss-offunction approach, the T-DNA insertion mutant lines with impaired ADH genes were used. The plants were exposed to polyethylene glycol-induced drought stress, and their responses at physiological, biochemical and molecular levels were analysed together with their overall growth performance. In the present study, the level of relative water content (RWC) of Arabidopsis plants dropped to 75% from the initial level of 85% when treated with 5% (w/v) PEG-20,000, demonstrated that the plants were moderately water-stressed. The stressed plants had high levels of proline and low levels of chlorophyll. At enzyme and metabolite levels,both the root and leaf NADH-ADH activities were increased 5.9 and 4.4 folds,respectively. For pyruvate decarboxylase (PDC), the activity was increased in the root (1.2 folds) and in the leaf (4.4 folds). Ethanol, the end product of ethanol fermentation was accumulated in both the leaf (3 folds) and root (2 folds). The increase in the level of ethanol was parallel with the increase observed in the activities of NADH-ADH and PDC. At gene level, the majority of the ADH and PDC genes were up-regulated. Two of the PDC genes (AT5G01320 and AT4G33070) genes and three of the ADH genes (AT1G64710, AT1G77120 and AT5G24760) were up-regulated in the leaf and root. These evidences support the conclusion that the capacity of ethanolic fermentation was enhanced in response to drought. When the individual ADH gene was defective, a severe reduction in the ADH activities and growth performance of the mutant plants were observed when exposed to drought. The T-DNA insertion adh knock-out mutant lines [adh1mutant (AT1G77120) and two adh-like mutants (AT1G64710 and AT5G24760)] demonstrated reduced growth judging by a shorter root system and lower biomass content. The plants also failed to retain cellular water which subsequently affected their physiological process including photosynthesis. In the transgenic Arabidopsis plant over-expressing the ADH1 gene, the capacity of ethanolic fermentation was enhanced judging by the increase in the ADH enzyme activity (6 folds). Under drought stress, the transgenic plant exhibited the following phenotypic improvements i) improved ability to retain cellular water; ii) increased chlorophyll content; iii) increased proline level; iv) increased NADH-ADH activity;v) increased volume of root system and iv) increased biomass. All these features contributed to the overall improvement of the transgenic plants under drought. As a conclusion, ethanolic fermentation is important for plants grown under drought condition. Enhancing the capacity of ethanolic fermentation improves plant ability to maintain cellular water; thus, supports the normal function of photosynthesis. To reduce the impacts of drought in plants, the capacity of plant ethanolic fermentation may be enhanced, and this strategy could be implemented in crop plants of economic importance.